2022
DOI: 10.22159/ijpps.2022v14i11.45593
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Screening of Anti-Inflammatory Activity of Methanolic and Aqueous Extracts of Anogeissus Latifolia Leaves

Abstract: Objective: To evaluate and compare anti-oxidant and anti-inflammatory activity of methanolic and aqueous extract of Anogeissus latifolia leaves Methods: The in vitro antioxidant activity was investigated using nitric oxide radical inhibition activity assay, hydroxyl radical scavenging activity assay, DPPH free radical scavenging assay, and reducing power assay. The in vitro anti-inflammatory activity was investigated using erythrocyte membrane stabilization, inhibition of protein denaturation, and proteinase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In their study, aqueous extract and methanolic extract of kenaf leaves at concentrations of 200-400 mg/kg were used to treat carrageenan-induced rat paw oedema. At the highest treatment concentration, kenaf leaf methanolic extract and aqueous leaf methanolic extract showed to inhibit rat paw oedema at 52% and 49%, respectively, which ultimately exemplified the extracts' anti-inflammatory activities [40].…”
Section: Immunomodulatory Effects Leaf Extractmentioning
confidence: 76%
See 1 more Smart Citation
“…In their study, aqueous extract and methanolic extract of kenaf leaves at concentrations of 200-400 mg/kg were used to treat carrageenan-induced rat paw oedema. At the highest treatment concentration, kenaf leaf methanolic extract and aqueous leaf methanolic extract showed to inhibit rat paw oedema at 52% and 49%, respectively, which ultimately exemplified the extracts' anti-inflammatory activities [40].…”
Section: Immunomodulatory Effects Leaf Extractmentioning
confidence: 76%
“…Thus, the study suggested that kenaf leaf extract may be able to modulate macrophage-mediated responses, which indirectly relates to its immunomodulatory effect. In fact, the inhibition of the inflammatory responses of kenaf leaf extract was proven in vivo by Shaikh, et al [40]. In their study, aqueous extract and methanolic extract of kenaf leaves at concentrations of 200-400 mg/kg were used to treat carrageenan-induced rat paw oedema.…”
Section: Leaf Extractmentioning
confidence: 99%